2023
DOI: 10.1021/acsaem.3c01150
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Ag–Cu Bimetallic Nanoparticles on p-Si Photoelectrodes for Solar-Driven CO2 Reduction

Harsh A. Chaliyawala,
Stéphane Bastide,
Diane Muller-Bouvet
et al.

Abstract: In the present work, we report the one-step synthesis of Ag x Cu100–x bimetallic nanoparticles (NPs) on p-type silicon (p-Si) supports and their application as photocathodes for the photoelectrochemical CO2 reduction reaction (PEC-CO2RR). Based on the metal-assisted chemical etching (MACE) of Si in HF medium, the proposed method allows the formation of NPs homogeneously distributed on the Si surface, with an excellent control of their bimetallic composition, surface coverage, and morphology by adjusting the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“… SEM images of (a) Ag nanoparticles Reproduced from Ref [164] . Copyright©2020, Elsevier B.V (b) Ag−Cu nanoparticles Reproduced from Ref [184] . Copyright© 2023, American Chemical Society(c) Cu nanoparticles Reproduced from Ref [185] .…”
Section: Surface Chemistry Of Bimetallic Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“… SEM images of (a) Ag nanoparticles Reproduced from Ref [164] . Copyright©2020, Elsevier B.V (b) Ag−Cu nanoparticles Reproduced from Ref [184] . Copyright© 2023, American Chemical Society(c) Cu nanoparticles Reproduced from Ref [185] .…”
Section: Surface Chemistry Of Bimetallic Catalystmentioning
confidence: 99%
“…[164] Copyright©2020, Elsevier B.V (b) AgÀ Cu nanoparticles Reproduced from Ref. [184] Copyright© 2023, American Chemical Society(c) Cu nanoparticles Reproduced from Ref. [185] with permission from the Royal Society of Chemistry.…”
Section: Degradation Of Dye By Ag-based Bimetallic Catalystmentioning
confidence: 99%
“…[39] It is worth mentioning that AgÀ Cu bimetallic nano-nanoparticles modified p-Si photocathode was developed and used for PEC reduction of CO 2 . [40] Graphene as a new type of electrocatalyst also has outstanding performance in the PEC reduction of CO 2 . Yang et al used N-doped graphene quantum sheets (N-GQSs) as heterogeneous electrocatalysts to modify p-type Si nanowires, achieving a Faraday efficiency of up to 95 % for PEC reduction of CO 2 to CO at a low potential.…”
Section: Si-based Photoelectrodes Pec Reduction Of Co 2 To Comentioning
confidence: 99%
“…Recent advances in PEC CO 2 RR have shown that different products are possible depending on the cocatalyst used. [27][28][29] The most commonly used cocatalysts are Au, [30][31][32][33][34][35][36] Cu, [37][38][39] Ag, [39][40][41] and different molecular catalysts. [42][43][44][45] Aside from choosing the appropriate cocatalyst, it was reported that tuning the interface exposed to the electrolyte can also have an impact by stabilizing the reaction intermediate (i.e., *COOH from CO 2 ), which can lead to lower overpotential and higher Faradaic efficiency.…”
Section: Introductionmentioning
confidence: 99%